CAPITAL STRUCTURE DETERMINANTS AN EMPIRICAL INVESTIGATION OF INDONESIAN MANUFACTURING COMPANIES - Nana Umdiana; Kodriyah (ZILLZELL MEDIA PRIMA, 2026)
The purpose of this study is to empirically test the determination of the existing capital structure in manufacturing companies in Indonesia. Various capital structure theories (trade-off theory, pecking order theory, agency theory, and free cash flow theory) are reviewed in order to formulate testable hypotheses about the determinants of capital structure in manufacturing firms. The research was carried out on a sample of 896 financial statements using panel data procedures. The results show that Tangibility and liquidity have a significant negative effect on leverage. Profitability and company age have no effect on leverage, while company size has a significant negative effect. This study has laid some groundwork for further investigation into the determinants of capital structure in Indonesian firms, which could be the basis for a more detailed evaluation. Furthermore, empirical findings should assist corporate executives in making the best capital structure decisions. To the best of the authors' knowledge, this is the first study that uses the most recent data to investigate the determinants of capital structure of manufacturing firms in Indonesia. Furthermore, this study appears to confirm that the same factors influence capital structure decisions in developing countries as they do in developed economies.